Enhanced effect of nano-monetite hydrosol on dentin remineralization and tubule occlusion. Issue 6 (June 2020) - Tan, Shenglong; Chen, Shangsi; Wang, Yifan; Wu, Feige; Shi, Yufei; Wang, Jianglin; Du, Yinyin; Zhang, Shengmin
Highlights: Nano monetite particles with good dispersion can exist as hydrosol. Compared with nano hydroxyapatite hydrosol and bioactive glass, dentin tubule can be effectively occluded by nano monetite hydrosol in short time. Supersaturated ionic environment (Ca 2+ and PO4 3− ions) and remineralization activity supported from nano monetite hydrosol were beneficial to acid erosion resistance of dentin tubule. Abstract: Objectives: We aim to investigate the dentin tubule occlusion and remineralization potential of a novel nano-monetite hydrosol (nMH). Methods: First, nano-monetite hydrosol (nMH) was fabricated by homogeneous precipitation method. Then, the effectiveness of toothpaste with nMH on improving remineralization was evaluated by the measurement of tubule occluding ratio and acid-resistant stability compared with dentifrices comprising nano-hydroxyapatite hydrosol (nHH) and bioactive glass (BG). To explain this result, we studied the ions releasing and remineralization based on gelatin scaffold among nMH, nHH and BG. Finally, the cytotoxicity of these three minerals on Human dental pulp stem cells (HDPSCs) was evaluated. Results: Processing for more than 7 days, the toothpaste containing nMH exhibited the significant remineralization potential and acid-resistant compared with two commercial de-sensitive dentifrices comprising nHH and BG. In addition, cytotoxicity test resulted that nMH has good cell compatibility to HDPSCs below extracts concentration of 3.12 mg/mL. Significance: Small size, the release of Ca 2+ and PO4 3− with high concentration, strongly binding on dental surface, and fast transformation to HAp, were all needed in the preparation of effective dentin tubule occluding biomaterials.